A Natural Jewel Threatened by Maritime Insecurity in the Gulf of Guinea - Musayyab, Said; Sutanto, Rudy; Susmoro, Harjo (Formosa Journal of Applied Sciences, 2024)
The Gulf of Guinea, an area rich in natural beauty and natural resources such as oil, gas, and fisheries, faces serious threats from widespread maritime piracy activities. The region is an important economic center, but maritime insecurity threatens its economic stability and development. Numerous regional and international initiatives have been undertaken to enhance security in these waterways, such as the Nigerian government's "Deep Blue" project and collaboration with the Economic Community of West African States (ECOWAS). The UN Security Council has also passed a resolution to address this threat. Despite this, challenges remain significant due to the high number of attacks and significant economic impact. Addressing this issue requires continued cooperation between countries in the Gulf of Guinea region and the international community to ensure security and sustainable exploration in this region​.